Impact of innovation platforms on marketing relationships:the case of Volta basin integrated crop-livestock value chains in northern Ghana - Adane-Mariami, Z. (Humboldt-Universität zu Berlin, 2013)
A recent trend in scientific and agricultural development approaches show a shift from linear transfer of technology models towards system thinking to improve livelihoods resilience of smallholder agriculturalists in developing countries, and thus to achieve sustainable food security. One manifestation of such shifts is the recognition of agricultural innovations as multi-dimensional and co-evolutionary processes which integrates technological, organizational, socio-economic and institutional innovations that can create synergies when applied jointly. This thesis attempts to test a new conceptual framework for evaluating innovation platforms (IPs) for agri-food value chains. The framework is based on the structure-conduct-performance hypothesis of industrial organization in combination with concepts from new institutional economics and marketing. Data to test the framework was collected through interviews of stakeholders of two IPs in the Volta Basin Development Challenge Program on integrated management of rainwater in crop-livestock agro-ecosystems in two northern regions of Ghana. The study used a mixed methods research methodology. A semi-logarithmic multiple regression analysis was employed to test relationships between the variables representing the structure, conduct and performance of the platforms following a principal components factor analysis to obtain reduced number of underlying factors from Likert-type statements on communication and information sharing (representing the conduct element) and improved market access (for performance). The qualitative information obtained through focus group discussions, interviews of platform facilitators and key respondents, and participant observation of an IP meeting also validates a possible link between the structure of the platforms, the conducts of their members, and the resulting market performance through reducing transaction costs of search and information. The econometric results also support this claim. Improvement in interaction or communication within IP, gender, the location of the IP, and household wealth were found to have a significant effect on members’ access to market. Due to the short life of the project and the small number of people involved in the IPs, it is difficult to come to a strong conclusion on whether the framework is most appropriate for conducting an impact evaluation, or if at all, the results so far achieved are significantly associated to the intervention. This suggests the need for further work to refine and test the framework extensively through impact evaluation of completed projects or projects with relatively longer life; and also assess the overall impact of the IPs including environmental, social, and project sustainability. However, given the theoretical support from well-founded theories, the new framework could be used side by side with conventional methods of project evaluation to support existing approaches by producing complementary or supplementary results and help judge its suitability.